COMMUNAL ECCLESIOLOGY: The Church Responds to the Reality of Migration in Batak Land - Sinaga, Lamria (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
This paper aims to construct the church's response in facing the reality of migration in Batak land with the church's starting point as a community (communal ecclesiology). Communal ecclesiology requires an understanding of the cultural context and local wisdom of the community where the church grows. The context of the Christian community and churches in Batak land is characterized as communal life and thickened to the local wisdom. It is concluded that Christianity and churches in Batak land could adopt communal ecclesiology in response to the current migration reality. This article overviews the life of the early church in Acts. 2:41-47 as communal ecclesiology shows the Church's nature in celebrating personal faith communally within the faith community in three ways, namely daily labor, fellowship labor, and God's labor.